PENINGKATAN KETERAMPILAN BERBICARA BAHASA INGGRIS MELALUI METODE PEMBELAJARAN DISCOVERY LEARNING PADA SISWA KELAS IV SDIT CITRA AZ-ZAHRA JOGLO, JAKARTA BARAT - Khairunnisa, Khairunnisa (Jurnal Analisis Pendidikan Sosial, 2024)
Increasing Students English Speaking Skills Through Discovery learning in the Fourth Grade of SDIT Citra Az Zahra. This research aims to: 1) design the lesson planning, 2) analyse learning implementation, 3) analyse the increasing of students speaking skills score by using discovery learning method. The subject is the Fourth grade of SDIT Citra Az Zahra students and there are 24 students. This research is classroom action research that consists of three cycles. Discovery learning cycle I the students make a group for discussing about dialogue formal and informal in daily activities using phone. Discovery learning cycle II the students make a role reversal. Discovery learning cycle III the students make a dialogue with the correct order and role reversal with the group. Data were collected using observation and tests, and the qualitative descriptive analysis was then used to analyse the collected data. Results of this study shows that: 1) learning planning design is in accordance to the students characteristic in which students speaking skills are low and they are not active in speaking English , 2) learning process by using Discovery learning has increased students activities in learning through observing the objects, observing the action, using the various of vocabularies, giving command, accuracy and speed of carrying out the instructions and asking question activity, 3) the assessment instrument use oral practice, essay test, and description test with a validity value of 0.853, a reliability value of 0.99, average difficulty level of items value of 62,50, and a well acceptable discrimination power of items value of 0,669, 4) the improvement of the speaking abilities can be seen from various aspects: comprehension, fluency, pronunciation, and vocabulary in the first cycle 22,73%, the second cycle 54,54% and the third cycle 81,81%.